Individual and group‐level job resources and their relationships with individual work engagement. Issue 3 (16th June 2016) - Füllemann, Désirée; Brauchli, Rebecca; Jenny, Gregor J.; Bauer, Georg F.
Abstract : Objectives: This study adds a multilevel perspective to the well‐researched individual‐level relationship between job resources and work engagement. In addition, we explored whether individual job resources cluster within work groups because of a shared psychosocial environment and investigated whether a resource‐rich psychosocial work group environment is beneficial for employee engagement over and above the beneficial effect of individual job resources and independent of their variability within groups. Methods: Data of 1, 219 employees nested in 103 work groups were obtained from a baseline employee survey of a large stress management intervention project implemented in six medium and large‐sized organizations in diverse sectors. A variety of important job resources were assessed and grouped to an overall job resource factor with three subfactors (manager behavior, peer behavior, and task‐related resources). Data were analyzed using multilevel random coefficient modeling. Results: The results indicated that job resources cluster within work groups and can be aggregated to a group‐level job resources construct. However, a resource‐rich environment, indicated by high group‐level job resources, did not additionally benefit employee work engagement but on the contrary, was negatively related to it. Conclusions: On the basis of this unexpected result, replication studies are encouraged and suggestions for future studies on possible underlying within‐group processes are discussed. The study supports the presumed value of integrating work group as a relevant psychosocial environment into the motivational process and indicates a need to further investigate emergent processes involved in aggregation procedures across levels.